Organized Activity Involvement Among Rural Youth: Gender Differences in Associations Between Activity Type and Developmental Outcomes - Kaitlyn A. Ferris; Benjamin Oosterhoff; Aaron Metzger (Journal of Research in Rural Education, 2013)
The current study examined associations between organized activity involvement, academic achievement, and problem behavior in a sample of youth from a non-agricultural based rural community (Mage = 15.26, Age range = 11-19 years, N = 456). Analyses examined whether associations varied as a function of adolescent gender and age. Participants reported their involvement in a broad range of organized activities across multiple contexts, including community and school clubs, volunteering, arts/music, and church and sports involvement. Results from a multi-group structural equation model controlling for adolescent age and parental education indicated that for all youth, participation in school clubs was associated with higher grade point average (GPA), and church involvement was associated with lower problem behavior. For boys, church involvement and arts/music were associated with higher GPA, and volunteering was associated with lower GPA. For girls, participation on sports teams was associated with higher GPA and lower levels of problem behavior. Several of these findings differ from previous organized activity research on urban and suburban youth, indicating that involvement in organized activities provides unique developmental benefits for adolescent boys and girls living in a rural context.